Jordan : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This Report on the Observance of Standards and Codes (ROSC) provides a review of Jordan's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of quality of national accounts, consumer and producer price indices, and government finance, monetary, and balance-of-payments statistics. The assessment reveals that Jordan participates in the GDDS and meets the recommendations for the coverage, periodicity, and timeliness of most data categories. Jordan's macroeconomic statistics also broadly meet the periodicity requirements of the SDDS.